ANALISIS KESULITAN BERBICARA BAHASA INGGRIS PADA SISWA BIMBINGAN BELAJAR FUN ENGLISH - Hesty Rohmatul Inayah (Asosiasi Dosen Muda Indonesia, 2024)
The aim of this research is to determine the difficulties students experience when speaking English and the factors that influence students' difficulty speaking English in Fun English tutoring students. This research was conducted on 11 Fun English tutoring students, using qualitative research methods. Data collection techniques in this research used questionnaires, interviews with students and documentation. The data analysis technique in this research uses data collection, data reduction, data presentation and drawing conclusions. Testing the validity of the data uses the Triangulation technique. The results of the research show that: The difficulties experienced by students in speaking English are difficulties in using grammar, difficulties in using vocabulary and also difficulties in pronunciation. The factors that cause students to have difficulty speaking English are lack of confidence, lack of mastery of vocabulary and also lack of motivation in speaking English.